Coadministration antagonist dopamine receptor D4 with CB2 receptor agonist decreases binge-like intake of palatable food in mice - Rodríguez-Serrano, Luis Miguel; López-Castillo, Ana Paola; Cabrera-Mejía, María Cristina; Cedillo-Figueroa, Ana Sofía; Zepeda-Ortigosa, Nyahn; Carregha-Lozano, Carolina; Chávez-Hernández, María Elena (Frontiers in Behavioral Neuroscience, 2025)
IntroductionFood intake is regulated by two systems: homeostatic and hedonic. An imbalance between these systems can induce overconsumption, such as binge eating disorder (BED), and is associated with dysregulation of the dopamine reward system. The cannabinoid type 2 receptor (CB2R) has been identified in dopamine neurons and may play an important role in motivated behaviors, including food intake. Nevertheless, the interaction between the dopamine D4 (DRD4) receptor and CB2R in binge-like intake has not yet been identified. Therefore, the present study aims to evaluate the effects of intraperitoneal administration of DRD4 antagonist (L-745870), as well as the coadministration of DRD4 antagonist with either CB2R agonist (HU308) or antagonist (AM630), on binge-like intake of palatable food (PF) in adult male mice.MethodsWe used adult male 34 C57BL6/J mice. All animals were housed individually and had ad libitum access to standard diet (SD) and water. To evaluate binge-like intake, the animals had 1 h of access to PF during 12 baseline binge eating test (BET) sessions. Mice were then randomly assigned to the following treatment groups: 1) vehicle; 2) L-745870; 3) L-745870-HU308, 4) L-745870+AM630 to be evaluated under the effect of treatments for three additionally BET sessions.ResultsOur results show that DRD4 antagonist reduced binge-like intake of PF, and that a coadministration with a CB2R agonist induced an even more pronounced reduction of binge-like intake.ConclusionThese findings suggest an interaction between the dopaminergic and endocannabinoid systems in the modulation of binge-like intake of PF in adult mice, where CB2R activation participates in modulating reward pathways and reducing binge-like behavior.